1996
DOI: 10.1111/j.1600-0714.1996.tb00209.x
|View full text |Cite
|
Sign up to set email alerts
|

A study on betel quid chewing behavior among Kaohsiung residents aged 15 years and above

Abstract: A telephone survey was used to study betel quid chewing behavior of Kaohsiung residents aged 15 and above in early 1991. Among the 1,162 subjects, 154 (13.3%) reported that they chewed betel quids and most of them (145/154) were men. Among the chewers, 33 (21.4%) indicated that they chewed it daily; all were men. Age distribution of the chewing behavior suggested that more young people chewed it at the time of the survey than had been the case in the past. The demographic distributions of betel quid chewing be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(24 citation statements)
references
References 22 publications
2
21
1
Order By: Relevance
“…The prevalence of betel quid chewing was similar to that reported for an older population (36.8±13.9 years) in an urban area in southern Taiwan (16% vs 13% for males and 1.3% vs 1.4% for females). 12 The prevalence of illicit drug use among adolescents in our study (0.6%) was much lower than the prevalence reported in the United Kingdom (5%) 13 and United States (4.8%).…”
Section: Discussioncontrasting
confidence: 52%
“…The prevalence of betel quid chewing was similar to that reported for an older population (36.8±13.9 years) in an urban area in southern Taiwan (16% vs 13% for males and 1.3% vs 1.4% for females). 12 The prevalence of illicit drug use among adolescents in our study (0.6%) was much lower than the prevalence reported in the United Kingdom (5%) 13 and United States (4.8%).…”
Section: Discussioncontrasting
confidence: 52%
“…Based on data estimated from 1,299 subjects collected from the same community as our study, the prevalence of betel quid chewers was 6% (95% CI 4.6-7.1; inclusive of all ages and sexes) 30 . Another report from the same community indicated that there was a prevalence rate of 6.5% for daily chewers among 511 men, whereas none of 651 women chewed quid daily 8 . The prevalence of betel quid chewing in our control group fell within the 95% CI values of these 2 reports.…”
Section: Discussionmentioning
confidence: 95%
“…The prevalence of HBsAg (22.1%) and anti-HCV (4.6%) in our healthy controls was similar to those in volunteer blood donors (Tsai et al, 1997b) or community controls in the same area (Tsai et al, 1993(Tsai et al, , 1996a(Tsai et al, , 1996b. The estimated prevalence of current betel Mann-Whitney U test was used for comparison of continuous data, whereas χquid chewers in the same community inhabitants was around 6.5% (Ko et al, 1992;Chen and Shaw, 1996). Moreover, the higher the educational level achieved, the lower the likelihood of being a betel quid chewer (Ko et al, 1992).…”
Section: Discussionmentioning
confidence: 99%